Economic Strategy for Cocoa Bean Downstream Productivity in Alur Cucur Village, Aceh Tamiang: Strategi Ekonomi Produktivitas Hilirisasi Biji Kakao di Kampung Alur Cucur Aceh Tamiang - Syarifah Yusra; Putri Amilda; Elisa Putri; Ulfah Raini (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
This Community Service (PKM) activity was carried out in Alur Cucur village, Aceh Tamiang Regency, an area with great potential for cocoa commodity development. However, local farmers still face various obstacles, such as limited market access, low cocoa bean selling prices, and the lack of processed product innovation. Through this program, the PKM Team of the Cut Nyak Dhien University of Science provided assistance to the Buloh Tamiang Farmers Group to increase the added value of cocoa beans through training in chocolate making, packaging, and digital marketing. The implementation method included an initial survey, socialization, production training, packaging technique assistance, and monitoring and evaluation. In addition, partners received production equipment that can be used to support business sustainability. The results of the activity showed an increase in partners' skills and knowledge in the process of processing cocoa into chocolate bars and powder, including an understanding of the manufacturing process, as well as hygienic and attractive packaging techniques with aluminum foil. Partners' understanding of promotion through digital media such as WhatsApp Groups, Instagram, and other digital platforms, also increase. This program successfully increased partners' motivation and independence in developing cocoa processing businesses. Going forward, follow-up measures in the form of further training, product innovation, and expansion of partnership networks are needed so that the development of the local chocolate industry can be sustainable and provide a significant economic impact for the people of Aceh Tamiang.